RESEARCH ON UAV IN LOGISTICS DISTRIBUTION - Haoyang, Li (Science-based technologies, 2023)
This article takes the COVID-19 epidemic as the starting point, and analyzes the difficulty of delivering drones in the "last mile" in the context of a severely aging population. The last mile delivery means that after customers shop through e-commerce, the purchased items are delivered to the distribution point, and then the goods are delivered to the customer from a sorting center through a certain means of transportation to achieve door-to-door service. The "last mile" of distribution is not a real mile, but refers to the distance from the logistics sorting center to the customer, and the process of delivering the goods to the customer through the means of transportation. Because it is a short distance, it is called one-kilometer delivery as the saying goes. This short-distance distribution is the last link of the entire logistics link and the only link that directly contacts customers face-to-face, which is of great significance. With the maturity of artificial intelligence technology, UAV distribution has emerged. This paper expounds the distribution scope, distribution process and technical equipment of the current development of UAV distribution, analyzes the problems of UAV endurance, airspace restrictions, and distribution safety, and puts forward corresponding countermeasures. Intelligent computing can reconstruct the logistics operation process. With the development of artificial intelligence, the logistics process may be decomposed into several parallel processes. Within the scope of the logistics system, using artificial intelligence technology, many activities such as automatic decision-making, automatic detection, and automatic repair can be automatically sorted according to the process. These activities can also not enter the cloud computing center platform, greatly improving the system computing efficiency and responsiveness. Because of its light weight and fast speed, UAVs can avoid urban traffic congestion and can cross special terrains such as mountains and lakes. The use of UAVs can shorten logistics delivery time and reduce logistics costs, so that its application scope of logistics distribution is getting wider and wider. In recent years, due to the strong contagiousness of the new crown epidemic, contactless distribution has attracted widespread attention, which has promoted the promotion and application of cutting-edge logistics distribution tools such as drones, drone vehicles and delivery robots.